3x-y=6and2x-y=-1solve by substitution metheod​

Question

3x-y=6and2x-y=-1solve by substitution metheod​

in progress 0
Piper 3 months 2021-11-10T18:40:29+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-11-10T18:42:19+00:00

    Answer:

    3x=y+6.

    x=y+6/3 put in into 2nd equation

    2(y+6/3)-y=-1

    y=9 than put it into any equation

    3x-9=6

    x=5

    0
    2021-11-10T18:42:22+00:00

    Given equations

    3x-y=6\\\implies -y=6-3x\\\implies y = 3x-6

    2x-y=-1

    Substituting the value of y, we get,

    \implies 2x-(3x-6)=-1\\\implies 2x-3x+6=0\\\implies -x+6=0\\\implies -x=-6\\\implies x= 6

    Substituting the value of x, we get,

    y = 3(6)-6\\\implies y = 18-6\\\implies y = 12

    \boxed{\boxed{\bold{Therefore, \ the \ values \ of \ x \ and \ y \ are \ 6 \ and \ 12 \ respectively}}}}}}}}}}

                                                                             

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )